Structural Properties, Production, and Commercialisation of Invertase - Wei, Cheng Pang; Aizi Nor Mazila, Ramli; Nur Dini, Johar (Universiti Kebangsaan Malaysia, 2019)
The knowledge gained from yeast fermentation made invertase one of the earliest exploited enzymes in human history. Invertase functions as carbohydrases by hydrolysing sucrose into its simplest unit. Extensive studies on invertase have made it well-characterised through the discovery of its existence in a variety of living organisms. It is interesting to study the different types of invertase from either the same or different origins as they might have distinct properties and could possess unique characteristics. With the advancement in technology, the three-dimensional structure, catalytic domain, and mechanism of invertase action have been discovered. Furthermore, it is important to understand how this enzyme has been produced via fermentation or recombinant technology methods. Finally, invertase has been employed in several important industries and its future commercialisation is promising.